Three‐dimensional mapping of the attenuation coefficient in optical coherence tomography to enhance breast tissue microarchitecture contrast. Issue 6 (20th March 2020) - Foo, Ken Y.; Chin, Lixin; Zilkens, Renate; Lakhiani, Devina D.; Fang, Qi; Sanderson, Rowan; Dessauvagie, Benjamin F.; Latham, Bruce; McLaren, Sally; Saunders, Christobel M.; Kennedy, Brendan F.
Abstract: Effective intraoperative tumor margin assessment is needed to reduce re‐excision rates in breast‐conserving surgery (BCS). Mapping the attenuation coefficient in optical coherence tomography (OCT) throughout a sample to create an image (attenuation imaging) is one promising approach. For the first time, three‐dimensional OCT attenuation imaging of human breast tissue microarchitecture using a wide‐field (up to ~45 × 45 × 3.5 mm) imaging system is demonstrated. Representative results from three mastectomy and one BCS specimen (from 31 specimens) are presented with co‐registered postoperative histology. Attenuation imaging is shown to provide substantially improved contrast over OCT, delineating nuanced features within tumors (including necrosis and variations in tumor cell density and growth patterns) and benign features (such as sclerosing adenosis). Additionally, quantitative micro‐elastography (QME) images presented alongside OCT and attenuation images show that these techniques provide complementary contrast, suggesting that multimodal imaging could increase tissue identification accuracy and potentially improve tumor margin assessment. Abstract : For the first time, wide‐field 3D optical coherence tomography (OCT)‐based attenuation imaging of human breast tissue microarchitecture with co‐registered postoperative histology is demonstrated. The results show that attenuation imaging can delineate nuanced features within tumors (including necrosis and variations in tumor cell density and growth patterns) and benign features (such as sclerosing adenosis). Additionally, quantitative micro‐elastography (QME) images are presented alongside OCT and attenuation images, showing the complementary contrast provided by these techniques.